KAJIAN ESTETIKA BENTUK PADA FASADE PERUMAHAN REAL ESTATE DI YOGYAKARTA - Sastra M, Suparno (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
Technology in construction and building materials was instrumental in the development of the design and periodization of architectural style. Particularly in housing, development in the physical infrastructure of housing such as real estate building in various housing complexes in Yogyakarta already generated diversity in facade design and various types of the arrangement of architectural elements that are very phenomenal. Therefore, this study is so important and necessary to conduct in order to (a) find out the principles of the arrangement of architectural elements in real estate building facade, and (b) describe the identification of the architectural elements forming a configuration of real estate building faí§ade. The study used an explorative method for exploration on field and made a qualitative analysis to find the facts. Areas of the study include the four residential real estate locations in Sleman Regency, Yogyakarta province. The study was conducted in the housings of Gejayan Puri Indah, Casa Grande, Bale Hinggil Residence, and Hyarta Residence. The samples were standardtype buildings, because it is expected to maximally represent diversity in housing design in the residential locations. The unit of analysis was building facades on four residential locations. Parameters of the architectural elements of the facade were roof, walls, columns, openings, main entrance, terrace and balcony, and ornamentation. The arrangement of residential building facade elements was studied on the bases of symmetry, articulation, visual proportion, and horizontal-vertical direction. The results of the study were: first, the symmetry of a residential building facade shows an asymmetric tendency because of aesthetic considerations and the principles of construction as well as the intention to maximize a selling point. Second, all the building facades in the four residential locations have the strong articulation with focus on main entrance, terrace and balcony, railing, balcony and roof ornamentation as the main elements forming the facade articulation. Third, the visual proportion of facade was found to have more balanced tendency between roof and building body. Fourth, the facades of residential buildings have mostly had balanced horizontal-vertical directions because the height of building was almost equal to the width of the building and the arrangement of horizontal-vertical architectural elements forming the facade was averagely composed in a balanced manner.